Multiplanar and two-dimensional imaging of central airway stenting with multidetector computed tomography - Ozgul, Mehmet Akif; Ozgul, Guler; Cetinkaya, Erdogan; Abul, Yasin; Kirkil, Gamze; Seyhan, Ekrem Cengiz; Gul, Sule (Bmc, 2012)
Background: Multidetector computed tomography (MDCT) provides guidance for primary screening of the central airways. The aim of our study was assessing the contribution of multidetector computed tomography-two dimensional reconstruction in the management of patients with tracheobronchial stenosis prior to the procedure and during a short follow up period of 3 months after the endobronchial treatment. Methods: This is a retrospective study with data collected from an electronic database and from the medical records. Patients evaluated with MDCT and who had undergone a stenting procedure were included. A Philips RSGDT 07605 model MDCT was used, and slice thickness, 3 mm; overlap, 1.5 mm; matrix, 512x512; mass, 90 and kV, 120 were evaluated. The diameters of the airways 10 mm proximal and 10 mm distal to the obstruction were measured and the stent diameter (D) was determined from the average between D upper and D lower. Results: Fifty-six patients, 14 (25%) women and 42 (75%) men, mean age 55.3 +/- 13.2 years (range: 16-79 years), were assessed by MDCT and then treated with placement of an endobronchial stent. A computed tomography review was made with 6 detector Philips RSGDT 07605 multidetector computed tomography device. Endobronchial therapy was provided for the patients with endoluminal lesions. Stents were placed into the area of stenosis in patients with external compression after dilatation and debulking procedures had been carried out. In one patient the migration of a stent was detected during the follow up period by using MDCT. Conclusions: MDCT helps to define stent size, length and type in patients who are suitable for endobronchial stinting. This is a non-invasive, reliable method that helps decisions about optimal stent size and position, thus reducing complications.
Keywords: Airway obstruction; Endobronchial stent; Multidetector computed tomography (MDCT)